Impact of Slow Deep Breathing Exercises using Incentive Spirometry on Functional Capacity among Patients with Coronary Artery Disease - Zahra Abdulmunem Ahmed; Hussam Abbas Dawood (Kufa Journal for Nursing Sciences)
Introduction